Normalization of wastewater coagulation-flocculation trials and implications in terms of variability in treatment performance and comparison of commercial coagulants. Issue 25 (10th November 2021) - Mailler, Romain; Mèche, Perrine; Sauvignet, Philippe; Azimi, Sam; Rocher, Vincent
ABSTRACT: Normalizations by TSS or P-PO4 3- initial concentrations are consistent as they are correlated to the Jar-test performances. Jar-tests results are independent of the wastewater quality variations in terms of TSS and P-PO4 3- and independent of the WWTP origin of the water. A notable variability in the TSS results indicates that the pollutant's initial load has to be taken into account even with normalizations. This variability is lower with normalization by P-PO4 3-, indicating that this is the best indicator to consider. It is possible to determine that the optimal cation dosage is 60 mol Fe 3+ / kg P-PO4 3- as it guarantees a residual concentration of 0.7–1.0 mgP/L and a good removal of TSS. Then, six commercially available cationic coagulants were compared, demonstrating a comparable effect at a comparable normalized molar dose, whatever the coagulant on both TSS and P-PO4 3-, as well as on soluble carbon and nitrogen. The differences observed between these types of coagulants in the literature are then probably due to methodological issues. Settling velocity distribution charts were also very similar for the different coagulants. This confirms that the source of cation and the type of cation have no significant effect on physico-chemical settling performances. GRAPHICAL ABSTRACT: UF0001